2001
DOI: 10.1007/bf03192426
|View full text |Cite
|
Sign up to set email alerts
|

Habitat factors and the presence or absence of otters Lutra lutra in Denmark

Abstract: Habitat factors and the presence or absence of ottersLutra lutra in Denmark. Acta Theriologica 46: 171-179.The purpose of the present study was to examine the relative influence of different habitat factors on otters Lutra lutra (Linnaeus, 1758) and to develop a predictive model to better understand the distribution of the otter in Denmark. During the National Otter Survey in 1991 data were collected on 19 variables which reflected aspects of habitat structure, composition, organic pollution and human disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Among the locations assessed, the most frequent marine otter sign observed was spraints (77%), while direct observations were scarce. Spraints as an indicator of presence has been widely used in studies of otter from the genera Lontra and Lutra (Hong et al, 2020; Madsen & Prang, 2001). Spraints are considered conspicuous signs that assist the population assessment of elusive species such as otters.…”
Section: Discussionmentioning
confidence: 99%
“…Among the locations assessed, the most frequent marine otter sign observed was spraints (77%), while direct observations were scarce. Spraints as an indicator of presence has been widely used in studies of otter from the genera Lontra and Lutra (Hong et al, 2020; Madsen & Prang, 2001). Spraints are considered conspicuous signs that assist the population assessment of elusive species such as otters.…”
Section: Discussionmentioning
confidence: 99%
“…Madsen and Prang (2001) and Delibes et al (2009) concluded that otter must be treated with care as an indicator of good aquatic habitat quality. Despite that our research did not consider several important environmental parameters, such as water quality or food supply, the evident change in tolerance to habitat characteristics recorded in our study leads to a similar conclusion that presence–absence data for expanding otter populations should not be considered as a reliable indicator of habitat quality.…”
Section: Discussionmentioning
confidence: 99%
“…The markings of other otter species as Lontra provocax (Thomas, 1908), Lutra lutra (Linnaeus, 1758) and Lontra canadensis (Schreber, 1777) are usually found in areas with less concentrated vegetation, because their visual and scent markings can be better perceived by other individuals (Madsen & Prang 2001, Medina-Vogel et al 2003. However, individuals of the L. longicaudis species, studied by MacDonald & Mason (1987) and Spinola & Vaughan (1995), most often defecate in areas with greater vertical plant cover.…”
Section: Introductionmentioning
confidence: 99%